The Effect of Work Ability, Motivation And Physical Work Environment on Employee Productivity PT. Andhika Pratama Jaya Abadi Deli Serdang - Adjie Rahim Ramadhan; Toni Hidayat (International Journal of Economics (IJEC), 2022)
This study aims to determine: 1) the effect of work ability on employee productivity, 2) the effect of motivation on employee productivity, 3) the effect of the physical work environment on employee productivity, and 4) the influence of work ability, motivation, and the physical work environment simultaneously on employee productivity at PT.Andhika Pratama Jaya Abadi Deli Serdang The type of research used is quantitative research. The data used is primary data. The population is as many as 50 people and the sampling technique uses saturated samples where the entire population is used as respondents in the study. The analysis used the classical assumption test analysis method, multiple linear regression analysis, hypothesis testing and the coefficient of determination. The results concluded that work ability has a significant influence on employee productivity with a significance level of 0.017. Motivation has a significant effect on employee productivity with a significance level of 0.001. The physical work environment has a significant effect on employee productivity with a significance level of 0.034. Workability, motivation, and the physical work environment simultaneously have a significant effect on employee productivity at PT. Andhika Pratama Jaya Abadi Deli Serdang with a significance level of 0.000.